Penerapan Dan Pengelolaan Manajemen Resiko (Risk) Dalam Industri Perbankan Syariah: Studi Pada Bank BUMN dan Bank Non BUMN - tasriani tasriani (Lembaga penelitian dan pengabdian kepada Masyarakat, 2015)
This study used a qualitative research method that is research that aims to build a preposition and explain the meaning behind the social reality that happened. This research is digging deeper into the application of Islamic banking risk management at the Bank of SOEs and non-SOEs Bank. The focus of the studies in this research are: Practice implementation and governance of risk management, risk management practices carried out by Islamic banking has been able to reduce the risk of loss, and compliance with Islamic law (principle / principle of Islamic transactions).The results showed that banks in Indonesia have entered into the era of integrated risk management (integrated management) and risk-based supervision (risk based supervision). All products are issued by Bank Sharia SOEs and non-SOEs supervised by the Financial Services Authority (FSA) and Sharia Supervisory Board (DPS) in accordance with the functions and authority of each institution. The application of risk mitigation is happening in Islamic banking there is a risk that originated from internal employees or company caused by itself and external customers. The most highest risk of murabahah financing. The principle in Islamic transactions to the principles of fraternity, justice, welfare, balance and universality has been applied. Risk mitigation financing is done on fiduciary risk as the risk that is legally responsible for breach of contract investments of incompatibility with the provisions of sharia or mismanagement (mismanagement) to the investor funds.